Art, culture and etnodesarrollo:the pilot experience of mediation in bocas de ure, cordoba. (2018)
This text presents the transversal technical and methodological challenges that came together in the participatory articulation of the Ethnodevelopment plan and the exercise of empirical community museography for the population of Bocas de Uré, Córdoba. The results of focus groups, discussion tables, general decision-making assemblies and intensive workshops on creative narratives and illustration for memory were systematized. The process resulted in a pilot methodology of artistic mediation for the cultural memory and ethno-development of Afro-descendant communities in the Colombian Caribbean. © 2018 Universidad del Norte. All Rights Reserved.